Deprescribing for older people living in residential aged care facilities: Pharmacist recommendations, doctor acceptance and implementation. (April 2023) - Quek, Hui Wen; Etherton-Beer, Christopher; Page, Amy; McLachlan, Andrew J; Lo, Sarita Y; Naganathan, Vasi; Kearney, Leanne; Hilmer, Sarah N; Comans, Tracy; Mangin, Derelie; Lindley, Richard I; Potter, Kathleen
Highlights: Residents in residential aged care facilities are taking unnecessary medications that have the potential to cause harm. Pharmacists and GPs, as part of a multidisciplinary team, are well-positioned to evaluate polypharmacy and improve patient outcomes through deprescribing to reduce inappropriate polypharmacy. Pharmacist-led deprescribing recommendations arising from an algorithm-based medication review are acceptable to doctors and can have a significant impact on the number of inappropriate medications consumed by older people. Abstract: Background: Deprescribing is an intervention to address the high prevalence of inappropriate polypharmacy in older people living in residential aged care facilities (RACFs). Many deprescribing interventions are complex and involve several stages including initial pharmacist recommendation, subsequent acceptance of the recommendations by a prescriber and the patient, and then actual implementation. Objectives: This study aimed to investigate pharmacist deprescribing recommendations for residents within RACFs, general practitioner (GP) acceptance, and the actual implementation of the accepted recommendations at 12-month. Methods: The intervention occurred as part of a randomised controlled trial and comprised a pharmacist-led medication review using an evidence-based algorithm, with the focus on identifying medications to potentially deprescribe. Consent to participate was obtained from residents (or surrogate decision-makers), RACF nursing staff and the resident's GP. Deprescribing recommendations were reviewed by GPs before implementation as part of the intervention and control arms of the trial, although control group participants continued to receive their usual medications in a blinded manner. Results: There were 303 participants enrolled in the study, and 77% (941/1222) of deprescribing recommendations suggested by the pharmacists were accepted by GPs. Of the recommendations accepted by GPs, 74% (692/ 941) were successfully implemented at the end of the follow-up visit at 12 months. The most common reason for deprescribing was because medications were no longer needed (42%, 513/ 1231). Conclusion: Pharmacist-led deprescribing recommendations arising from an algorithm-based medication review are acceptable to doctors and can have a significant impact on reducing the number of inappropriate medications consumed by older people in RACFs. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12613001204730